2010
DOI: 10.1073/pnas.1000401107
|View full text |Cite
|
Sign up to set email alerts
|

KDM8, a H3K36me2 histone demethylase that acts in the cyclin A1 coding region to regulate cancer cell proliferation

Abstract: Localized chromatin modifications of histone tails play an important role in regulating gene transcription, and aberration of these processes leads to carcinogenesis. Methylated histone lysine residues, a key player in chromatin remodeling, are demethylated by the JmjC class of enzymes. Here we show that JMJD5 (now renamed KDM8), a JmjC family member, demethylates H3K36me2 and is required for cell cycle progression. Chromatin immunoprecipitation assays applied to human genome tiling arrays in conjunction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
179
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 170 publications
(185 citation statements)
references
References 25 publications
5
179
1
Order By: Relevance
“…Warburg effect | aerobic glycolysis | breast cancer | cancer metabolism J MJD5 is a Jumonji C domain-containing dioxygenase shown to be involved in lysine demethylation (1)(2)(3) and hydroxylation functions (4). Although the exact cellular substrates and functions of JMJD5 remain unclear, JMJD5 was shown to positively regulate cyclin A1 but negatively regulate p53 and p21 (1)(2)(3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Warburg effect | aerobic glycolysis | breast cancer | cancer metabolism J MJD5 is a Jumonji C domain-containing dioxygenase shown to be involved in lysine demethylation (1)(2)(3) and hydroxylation functions (4). Although the exact cellular substrates and functions of JMJD5 remain unclear, JMJD5 was shown to positively regulate cyclin A1 but negatively regulate p53 and p21 (1)(2)(3).…”
mentioning
confidence: 99%
“…Although the exact cellular substrates and functions of JMJD5 remain unclear, JMJD5 was shown to positively regulate cyclin A1 but negatively regulate p53 and p21 (1)(2)(3). Knockdown of JMJD5 in Michigan Cancer Foundation (MCF)-7 cells inhibits cell proliferation (1), and JMJD5 −/− embryos showed severe growth retardation, resulting in embryonic lethality at the midgestation stage (3).…”
mentioning
confidence: 99%
“…22,23 Huang and colleagues reported that a functional nuclear localization signal (NLS) and a nuclear export signal (NES) reside in the N-terminal domain of JMJD5. 38 JMJD5 localization is tightly regulated by Importin a/b-and transportin-1-mediated nuclear import and CRC1-dependent nuclear export, suggesting that JMJD5 translocation in and out of the nucleus may be associated with a novel function.…”
Section: Discussionmentioning
confidence: 99%
“…JMJD5 has been reported to suppress gene transcription through its histone H3K36me2 demethylase activity, 22,25 or positively promote gene transcription through binding to gene promoters. 32 To investigate if JMJD5 regulates the transcription of MAP1B, we evaluated MAP1B expression in JMJD5-depleted cells, JMJD5-overexpressing cells, and control cells using RT-real time PCR.…”
Section: Jmjd5 Modulates the Stability Of Microtubules By Regulating mentioning
confidence: 99%
See 1 more Smart Citation